Evaluating the Impact of a Women's Empowerment Program on Environmental Sustainability through Eco-Friendly Fertilizer Production - Qomariah, Lailiatul; Rusdiana, Desi Ummi; Hasanah, Sitti Widatul; Alauddin Athallah, Afif Rafi; Putra, Bagas Permana; Sumiati, Ika Dewi; Sari, Eka Puspita Kartika; Pamungkas, Zakaria Sandy; Wahyuni, Sri (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Evaluating the Impact of a Women's Empowerment Program on Environmental Sustainability through Eco-Friendly Fertilizer Production. The high potential in Grenden Village as a corn producer has the side effect of increasing corn plant waste. Most people do not utilize corn waste, especially corn cobs. Corn waste is rich in organic matter and can be reused for plant fertilization. Corn cobs can be used as an alternative fertilizer that can replace the role of chemical fertilizers. PPK Ormawa Team of HMPS S1 Science Education ASE held training for village residents through the Gayati Women's School to provide education and practical activities to residents to utilize corn waste as organic fertilizer. This research aims to evaluate the effectiveness of a training program in teaching local women to utilize corn cobs as organic fertilizer. This research was conducted using a descriptive qualitative method that focuses on describing the results obtained in real terms based on conditions in the field. Data were collected through observation, activity documentation, and interviews. The implementation of the activity was carried out in Grenden Village, Puger District in August 2024. The target of this activity was mothers who were members of the Gayatri Women's School, totaling around 20 people. The object of this activity is corn cobs which are one of the local wastes in Grenden Village. Evaluation of this activity through the results of the pretest and post-test shows that education and training in making fertilizer from Corn Cobs have a positive impact on the community such as waste reduction, economic improvement, soil health, and empowerment education.